2019
DOI: 10.1101/835462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation severity spectrum of rare alleles in the human genome is predictive of disease type

Abstract: The human genome harbors a variety of genetic variations. Single-nucleotide changes that alter amino acids in protein-coding regions are one of the major causes of human phenotypic variation and diseases. These single-amino acid variations (SAVs) are routinely found in whole genome and exome sequencing. Evaluating the functional impact of such genomic alterations is crucial for diagnosis of genetic disorders. We developed DeepSAV, a deep-learning convolutional neural network to differentiate disease-causing an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 103 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…A recent study showed that mutation-tolerant genes exemplified by olfactory receptors ( i.e. , those with fewer disease mutations) tend to function in metabolism, whereas more mutation-intolerant genes tended to function in development and signal transduction pathways ( 37 ). These findings imply a higher fitness cost for mutations in developmental than in metabolic genes ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that mutation-tolerant genes exemplified by olfactory receptors ( i.e. , those with fewer disease mutations) tend to function in metabolism, whereas more mutation-intolerant genes tended to function in development and signal transduction pathways ( 37 ). These findings imply a higher fitness cost for mutations in developmental than in metabolic genes ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…The glucagon receptor ranked among the lowest on the list with only one known disease-associated mutation, rs1801483/G40ECDS associating with diabetes, recorded in DisGeNET (37). A recent study showed that mutation-tolerant genes exemplified by olfactory receptors, (i.e., those with fewer disease mutations), tend to function in metabolism, whereas more mutation-intolerant genes tended to function in development and signal transduction pathways (38).These findings imply a higher fitness cost for mutations in developmental than in metabolic genes (39).…”
Section: Class B1 Mutational Constraint Spectrummentioning
confidence: 99%
“…Evidently, the different hydrogenbonding and stacking in G/T and G/A mismatches results in different thermodynamic trends and the energy and structural information are the compositions of the following variables, such as bond angle energies, bond energies, planarity energies, dihedral angle energies, Van der Waals energies or/and electrostatic energies. These results indicate that duplexes containing mismatches are considerably destabilized (Figure 5) compared with their correctly paired parent the extent being dependent on the base composition and sequence of the The mismatch of DNA leads to alterations of amino acid properties and can cause a change in protein structure [45,46]. Consequently, SNP may affect enzyme activity through the modification of protein structure and function [47].…”
Section: Cyp3a4*1b Single Nucleotide Polymorphismmentioning
confidence: 99%
“…Due to the rarity of the variant, we performed additional genotyping for replication, whereby the variant replicated for hemorrhagic stroke (p-value=0.02, N=3,263). Recessive variants can have high mutation severity in comparison to e.g., autosomal dominant variants 33 . Therefore, we further considered a recessive inheritance model and identified a genome-wide significant variant on DHX8 intron with the minimal adjustment (rs1728177, p-value=7.19×10 -9 , MAF=26%) (Extended Data Fig.…”
Section: Single Variant Analysesmentioning
confidence: 99%